Maintaining Health and Well-Being by Putting Faith into Action During the COVID-19 Pandemic - Koenig, Harold G. (Journal of religion and health, 2020)
Anxiety and fear adversely affect the physiological systems that protect individuals from infection. This article comments on the role that religious faith and practice can play in helping individuals remain free from infection by the coronavirus and in helping to moderate the effects of infection if that should occur. The author provides six recommendations to help individuals maintain spiritual, mental, and physical resilience during these anxious times of the COVID-19 pandemic.